Epidermal T Cell Dendrites Serve as Conduits for Bidirectional Trafficking of Granular Cargo - Chodaczek, Grzegorz; Toporkiewicz, Monika; Zal, M. Anna; Zal, Tomasz (Frontiers in Immunology, 2018)
Dendritic epidermal T cells (DETC) represent a prototypical lineage of intraepithelial γδ T cells that participate in the maintenance of body barrier homeostasis. Unlike classical T cells, DETCs do not recirculate and they remain persistently activated through their T cell receptors (TCR) at steady state, i.e. in absence of infection or tissue wounding. The steady state TCR signals sustain the formation of immunological synapse-like phosphotyrosine-rich aggregates located on projections (PALPs) which act to anchor and polarize DETC’s long cellular projections toward the apical epidermis while the cell bodies reside in the basal layers. The PALPs are known to contain pre-synaptic accumulations of TCR-containing and lysosomal granules, but how this cargo accumulates there remains unclear. Here, we combined anti-Vγ5 TCR, cholera toxin B (CTB) and LysoTracker-based intravital labeling of intracellular granules with high resolution dynamic microscopy and fluorescence recovery after photobleaching (FRAP) to characterize the steady state composition and transport of DETC granules in steady state epidermis. Intradermal fluorescent Vγ5 antibody decorated DETCs without causing cellular depletion, dendrite mobilization or rounding up and became slowly internalized over 48 hours into intracellular granules that, after 6 days, colocalized with LAMP-1 and less so with LysoTracker or early endosomal antigen-1. Intradermal CTB was likewise internalized predominantly by DETCs in epidermis, labeling a partly overlapping set of largely LAMP-1+ intracellular granules. These as well as LysoTracker-labeled granules readily moved into newly forming dendrites and accumulated at the apical endings. FRAP and spatiotemporal tracking showed that the inside tubular lengths of DETC cellular projections supported dynamic trafficking of lysosomal cargo toward and away from the PALPs, including internalized TCR and lipid raft component ganglioside GM1 (CTB). In contrast, the rate of GM1 granules transport through comparable dendrites of non-DETCs was twice slower. Our observations suggest that DETCs use chronic TCR activation to establish a polarized conduit system for long-range trans-epithelial transport aimed to accumulate mature lysosomes at the barrier-forming apical epidermis. The biological strategy behind the steady state lysosome polarization by DETCs remain to be uncovered.